Assessment of 13 Forensic Molecular Markers for skin colour in South Africa - Pharo, Gavin (Division of Forensic Medicine and Toxicology, 2019)
Molecular phenotyping is the use of informative genetic variation to estimate appearance. This concept can be applied in a forensic context to predict the appearance of suspects or decayed deceased individuals, which would otherwise remain unidentifiable. This concept has importance in a local context, as approximately 300 individuals remain unidentified, after conventional identification techniques, at Salt River Mortuary, every year. Ancestry Informative Markers (AIMs) are genetic variants with DNA which have been commonly associated with pigmentation phenotypes, and thus has value in predicting skin tone, hair colour and eye colour. This research study aimed to design and optimise an assay to genotype 13 AIMs associated with pigmentation, and then demonstrate the value of this assay by applying it to a case example and qualitatively predicting appearance. Primers were designed and PCR assays optimised to amplify each region, followed by Sanger sequencing on a case example. The case was that of an abandoned neonate, with unknown sex and ancestry. A comparison of the obtained genotypes to previous literature was performed to qualitatively estimate the skin tone, eye colour and hair colour of the decedent, which was not only in agreement with the forensic pathologist’s interpretation of sex and ethnicity, but provided richer detail with regards to ancestry, skin tone, eye colour and hair colour. The PCR assays were then further optimised into four multiplex assays with the intention of genotyping these AIMs by two SNaPshot® PCR assays (Applied Biosystems) in a larger control cohort to model the relationship between these AIMs and melanin index more objectively. Unfortunately, the scope of this research project did not allow for the completion of this additional aspect. Overall, these results indicate that these 13 AIMs have potential to predict pigmentation phenotypes of South African individuals. However, genotyping and modelling of the effects of these AIMs should be performed on a large cohort to further strengthen this conclusion.